PRIMARY IMMUNODEFICIENCY IN CHILDHOOD - Barros de Sá, Janilson; Guilherme de Sá Santos, João; Carvalho de Sá, Vinícius (Health and Society, 2024)
Primary immunodeficiencies (PIDs) represent a heterogeneous group of genetic diseases that compromise the function of the immune system, especially in childhood, when they are most frequently diagnosed. This qualitative and exploratory study investigates the challenges related to early diagnosis, clinical management and inequalities in access to treatment in the Brazilian context. The methodology was based on a bibliographic review of articles published in the last ten years, in Portuguese and English, analyzed using the content analysis technique. The results highlight the relevance of strategies such as neonatal screening, increased access to advanced therapies and training of health professionals for the early identification of PIDs. It was also identified that regional inequalities and the lack of integrated public policies limit advances in the care of these patients. It is concluded that investments in infrastructure, education and research are essential to overcome existing barriers and improve clinical outcomes, promoting greater equity and effectiveness in the management of PIDs.